PERBANDINGAN PENGETAHUAN MANAJEMEN LAKTASI PADA IBU POST PARTUM YANG MENDAPATKAN KONSELING DENGAN MEDIA AUDIO VISUAL DAN BOOKLET - Emilda, Sri; Anggeni, Untari; Tuti Ani, Eka (LPPM STIKes Mitra Adiguna, 2025)
The implementation of education on lactation management that has been taking place in health services is considered less than successful because the education provided is less interesting to mothers and is only one-way, resulting in ineffective communication between mothers and midwives. The purpose of this study was to compare knowledge of lactation management in post partum mothers who received counseling using audio visual media and booklets. This study uses a quantitative approach. The design used in this study was a Quasi-Experimental research design using a pre-post design to compare the actions taken before and after being given treatment and using the one group design and two group designs to differentiate the results of the post audiovisual group with booklets and samples grouped by 30 people. The results obtained from the bivariate analysis of the Wilcoxon test statistic test obtained a value of p = 0.001, meaning <0.05, meaning that there was an influence on knowledge of lactation management for post partum mothers before receiving counseling with audio-visual media. there is an effect of knowledge of lactation management of post partum mothers before receiving counseling with bookleat media and the Mann Whitney test statistic getting a p value = 0.037 <0.05, meaning that there is a difference in knowledge of lactation management in post partum mothers who receive counseling on audio visual media and booklets. Suggestions for health workers, especially midwives, especially those at PMB CH Mala Palembang, can provide counseling to post partum mothers regarding lactation management by using audio-visual media and booklet media.